Case of a cardiac arrest patient who survived after extracorporeal cardiopulmonary resuscitation and 1.5 hours of resuscitation: A case report. Issue 47 (November 2017) - Moon, Seong Ho; Kim, Jong Woo; Byun, Joung Hun; Kim, Sung Hwan; Kim, Ki Nyun; Choi, Jun Young; Jang, In Seok; Lee, Chung Eun; Yang, Jun Ho; Kang, Dong Hun; Park, Hyun Oh
Abstract: Rationale: Per the American Heart Association guidelines, extracorporeal cardiopulmonary resuscitation should be considered for in-hospital patients with easily reversible cardiac arrest. However, there are currently no consensus recommendations regarding resuscitation for prolonged cardiac arrest cases. Patient concerns and diagnosis: We encountered a 48-year-old man who survived a cardiac arrest that lasted approximately 1.5 hours. He visited a local hospital's emergency department complaining of chest pain and dyspnea that had started 3 days earlier. Immediately after arriving in the emergency department, a cardiac arrest occurred; he was transferred to our hospital for extracorporeal membrane oxygenation (ECMO). Interventions: Resuscitation was performed with strict adherence to the American Heart Association/American College of Cardiology advanced cardiac life support guidelines until ECMO could be placed. Outcomes: On hospital day 7, he had a full neurologic recovery. On hospital day 58, additional treatments, including orthotopic heart transplantation, were considered necessary; he was transferred to another hospital. Lessons: To our knowledge, this is the first case in South Korea of patient survival with good neurologic outcomes after resuscitation that lasted as long as 1.5 hours. Documenting cases of prolonged resuscitation may lead to updated guidelines and improvement of outcomes of similar cases in future.